Relations of the level of morphological differentiation and metabolic activity of squamous carcinomas of oropharyngeal areas according to positron emission tomography - M. Tisch; A.V. Lysak; O. O. Diadyk (Patologìâ)
Today verification and grading of oropharyngeal tumors, determination of their malignant potential remain an actual problem both in diagnostics and in predicting the growth of tumors.